Answer :
We know that
• Endpoint: (6, 1)
,• Midpoint: (-10, -3)
We use the midpoint formula to find the other end point.
[tex]M=(\frac{x_1+x_2}{2},\frac{y_1+y_2}{2})[/tex]Where,
[tex]\begin{gathered} M=(-10,-3) \\ x_1=6 \\ y_1=1 \end{gathered}[/tex]So, we have to find the coordinates for the second point. Let's replace all given information
[tex](-10,-3)=(\frac{6+x_2}{2},\frac{1+y_2}{2})[/tex]We solve x-coordinates and y-coordinates separately.
[tex]\begin{gathered} \frac{x_2+6}{2}=-10 \\ x_2+6=-20 \\ x_2=-20-6=-26 \end{gathered}[/tex][tex]\begin{gathered} \frac{y_2+1}{2}=-3 \\ y_2+1=-6 \\ y_2=-6-1 \\ y_2=-7 \end{gathered}[/tex]